Prevalence of cancer related fatigue and its associated factors among adult cancer patients in eastern Ethiopia: A cross-sectional study - Henok Legesse; Yalew Mossie; Lidia Tolessa; Deribe Bekele Dechasa; Lencho Ahmedin; Seblewengel Fita; Aminu Mohammed Yasin; Seid Tesi; Ahmed Hiko; Sisay Habte; Addisu Alemu; Ahmed Mohammed; et al. (PLoS ONE, 2026)
Background Fatigue is a frequent and distressing symptom experienced by patients with cancer. It may result from the disease process and/or its aggressive treatment, which substantially impact the quality of life of cancer patients. Furthermore, there is a paucity of evidence in the Eastern part of Ethiopia. Hence this study aimed to assess the prevalence of cancer related fatigue and its associated factors among adult cancer patients, Eastern Ethiopia. Methods Hospital based cross-sectional study was conducted from 1 st May to 30 th August, 2023 among 422 systematically selected cancer patients. Data were collected using structured, interviewer administered questionnaire. The outcome variable was evaluated using the Brief Fatigue Inventory (BFI). Binary logistic regression analyses were performed to examine the association between the explanatory variables and the outcome variable. Adjusted Odds Ratio (AOR) with 95% Confidence Interval (CI) at a P value less 0.05 was used to declare statistically significant association. Results Out of 422, 382 individuals with various cancer types participated in the study with a response rate of 90.5%. The prevalence of cancer related fatigue was found to be 71.2% (95%CI: 65.7–75.5). Rural residence (AOR = 2.84, 95%CI: 1.25–6.43), female sex (AOR = 3.25, 95%CI: 1.49–7.0), private occupational status (AOR = 6.44, 95%CI: 2.42–17.12), never used coffee (AOR = 7.02, 95%CI: 2.37–20.75), inpatient admission (AOR = 4.68,95%CI: 2.21–9.88) and advanced (AOR = 6.21, 95%CI: 2.61–14.78) & unclassified cancer stages (AOR = 4.84, 95%CI: 1.42–16.57) were significantly associated with cancer related fatigue. Conclusions Nearly three out of four cancer patients in Eastern Ethiopia experienced cancer related fatigue. The findings highlight the need for a supportive care service including psychosocial counseling and targeted intervention for high risk groups such as female, rural residents, inpatients, private workers and advanced cancer patients. Further research is warranted to explore the protective role of coffee consumption.